Penggunaan Media Jari Tangan dalam Meningkatkan Pemahaman Mekanisme Debit Kredit Mata Pelajaran Ekonomi Kelas XII - Hestysetyaningsih, Sri (Yayasan Sembilan Pemuda Indonesia, 2025)
Economic education in secondary schools often faces challenges in enhancing student engagement and ensuring a deep understanding of complex economic concepts. Understanding the principles of debit, credit, and normal balances in accounting, particularly when applied manually, involves illustrating and connecting each transaction with the debit-credit framework. This foundational concept in accounting is critical to ensure that transactions are recorded accurately in accordance with basic accounting principles. This study is a type of classroom action research aimed at addressing issues arising during the teaching and learning process. The subjects of the study were 31 students from class XII.8 at SMA Negeri 22 Palembang. These students served as both the focus and data sources for the research. Class XII.8 was chosen as the subject due to the heterogeneous characteristics of the students and their lack of attention during learning activities. Meanwhile, the object of the research was the teaching of Basic Accounting in the class. In the field of accounting, terms like “debit” and “credit” are commonly encountered. For the general public, these terms are often associated with money. In this context, when money is received, it is recorded as a debit, while when money is spent, it is recorded as a credit. Students unfamiliar with accounting often share this perspective. However, the debit-credit principle extends beyond money, involving five key account types essential to service companies. Understanding these accounts within service companies often poses challenges for students, particularly in terms of memorization. A practical method for overcoming this difficulty is utilizing the five fingers of the hand as a mnemonic device. Each finger can be linked to specific accounts, providing a relatable context to facilitate recall and comprehension.